2022
DOI: 10.3390/ijms23020937
|View full text |Cite
|
Sign up to set email alerts
|

Severe Natural Outbreak of Cryptocaryon irritans in Gilthead Seabream Produces Leukocyte Mobilization and Innate Immunity at the Gill Tissue

Abstract: The protozoan parasite Cryptocaryon irritans causes marine white spot disease in a wide range of fish hosts, including gilthead seabream, a very sensitive species with great economic importance in the Mediterranean area. Thus, we aimed to evaluate the immunity of gilthead seabream after a severe natural outbreak of C. irritans. Morphological alterations and immune cell appearance in the gills were studied by light microscopy and immunohistochemical staining. The expression of several immune-related genes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 62 publications
(101 reference statements)
2
12
0
Order By: Relevance
“…In addition, a similar phenomenon had been reported in yellowtail clownfish ( Amphiprion clarkii ) infected with C. irritans 24 . Non‐specific immunity provides the first line of defense against invading pathogens and it has been extensively studied 25 . C. irritans infection can induce a robust non‐specific immune responses for the ultimate survival of the infected host 26 .…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…In addition, a similar phenomenon had been reported in yellowtail clownfish ( Amphiprion clarkii ) infected with C. irritans 24 . Non‐specific immunity provides the first line of defense against invading pathogens and it has been extensively studied 25 . C. irritans infection can induce a robust non‐specific immune responses for the ultimate survival of the infected host 26 .…”
Section: Introductionsupporting
confidence: 63%
“…A study of gilthead seabream (Sparus aurata L.) detected focal hemorrhages at the base of the scales and gill cover and aggregation of erythrocytes in the dermal layer after the invasion of C. irritans. 25 In addition, with the presence of C. irritans in gills of E. coioides, accumulated mast cells (MCs) were detected at the site of parasites infection. 33 In another report, in situ hybridization (ISH) showed that, 34 In addition, after C. irritans infection, the result of immunohistochemical staining (IHC) showed that acidophilic granulocytes are mobilized and their presence was increased in gill of gilthead seabream.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…Especially, neutrophilic granulocytes are very effective in inflammatory reactions and the immune system. While the granulocytes are called innate immunity, leukocytes are termed in the acquired immune system [3].…”
Section: Introductionmentioning
confidence: 99%